2009
DOI: 10.1111/j.1365-2664.2009.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of riverine inland sand dune complexes: implications for the conservation of wild bees

Abstract: Summary1. The evaluation of restoration measures is an important task of conservation biology. Inland sand dunes and dry, oligotrophic grasslands have become rare habitat types in large parts of Central Europe and their restoration and management is of major importance for the preservation of many endangered plant and insect species. Within such habitats, it is important to restore key ecosystem services, such as pollination networks. As wild bees are the most important pollinators in many ecosystems, they rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
1
28
0
3
Order By: Relevance
“…In order to preserve C. montanus it is necessary to maintain the current management of sites where it still occurs and to implement extensive grassland management at sites where it declines. As the number of populations is still declining, habitat restoration is needed in order to reconnect wetland habitats (Exeler et al 2009). Our microhabitat data can help to make management recommendations for this endangered species.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In order to preserve C. montanus it is necessary to maintain the current management of sites where it still occurs and to implement extensive grassland management at sites where it declines. As the number of populations is still declining, habitat restoration is needed in order to reconnect wetland habitats (Exeler et al 2009). Our microhabitat data can help to make management recommendations for this endangered species.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Wild bees are particularly interesting for such a study as a strong decrease in their abundance and species richness has been reported in many parts of the world (e.g. Biesmeijer et al 2006, Cane andTepedino 2001).This seems to be particularly true for species that are highly specialized on specific pollen sources as larval food or special habitat structures to build their nests (Exeler et al 2009). As oligolectic bees are restricted to specific host plants, it has been proposed that they might be particularly prone to inbreeding and loss of genetic variability combined with a reduced gene flow among populations.…”
Section: Introductionmentioning
confidence: 96%
“…Some traditional agricultural habitats, which had been shaped by centuries of human influence (e.g. extensive hay meadows, dry oligotrophic grasslands or heathlands), have meanwhile become rare and fragmented (Exeler et al 2009). Species confined to such habitat types are, therefore, among those listed under the highest red list categories.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread decline of native bees ( Heithaus 1974, Banaszak 1996, Potts et al 2003, Fontaine et al 2006, Kremen et al 2007) and the spread of nonnative bees such as the European A. mellifera (Richardson et al 2000, Goulson 2003 have the potential to disrupt plant-pollinator relationships and exacerbate the global loss of biodiversity (Kearns et al 1998, Kremen et al 2007, Exeler et al 2009). However, the mechanisms by which invasive bees impact species interactions have received relatively little consideration in the context of areas undergoing large-scale restoration (Richardson et al 2000, Goulson 2003.…”
mentioning
confidence: 99%
“…Land-use change resulting from human activities affects not only the distribution of plant species, but also the behavioral and population ecology of plant pollinators, with the potential to limit or alter vital pollination services (Kearns et al 1998, Kremen et al 2007, Exeler et al 2009). Changes in both native and nonnative pollinator communities have been repeatedly demonstrated to have important cascading impacts on plant communities (Roubik 1980, Westerkamp 1991, Kearns et al 1998, Dick 2001, Goulson 2003, Traveset and Richardson 2006, Kremen et al 2007, Hanna et al 2013.…”
mentioning
confidence: 99%